GEOCHEMICAL FEATURES OF MAIKOP SERIES OF CRIMEAN AND BLACK SEA REGION - Mykhailov, V.; Zagnitko, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The geochemical features of the rocks of the Maikop series along sections of north-western shelf wells of the Black Sea (well Arkhangelsk-21, Golitsyn-1, 6, 7, 9, 12, 28), the central part of the Crimean peninsula (Dzhankojsky-1), Kerch Peninsula (Fontanovskaya-6, 12), the sea of Azov shelf (Severokazantipskaya-3), Prykerchenska section of the Black sea shelf (Subbotin-1) are studied. The studies found a high content of Corg (2,26–16,70 %) and TOC (1,5–10,2 %) in the rocks of the Maikop series, however, they usually are thermally immature and cannot be viewed as promising for oil shale research. Exceptions are rocks in the boreholes Golitsyn-1, 9, where the vitrinite reflectance reaches values typical of the lower part of the formation of the oil zone (0,8–1,8), indicating a favorable thermal conditions at the lower levels of Maikop deposits and their possible oil-and-gas potential. This is confirmed by the analysis of component composition of gas from wells Golitsyn-1, Arkhangelsk 21, Dzhankojsky-1, Severokazantipskaya-3, Subbotin-1. Here at considerable depths are present medium- and high gas content rocks, with an average recovery rate, with significant impurities homologues, some enriched with hydrogen sulfide, which indicates their prospects for gasand-oil content despite their thermal immaturity. This contradiction may be due to migration of gas and oil components from subsurface strata in the overlying horizons. Thus, at depths greater than 2000m, deposits of the Maikop series, on condition of the confirmation of significant volumes of rock rich in organic matter, can be viewed as promising for oil shale research. In regard to the Black Sea and the Crimean region, it may be noted that the discovered oil deposits are an indicator that deeper lying black shale deposits of the Albian and Maikop series have sufficient oil-and-gas potential and the optimal degree of thermal maturity, which corresponds to the main zone of oil formation, and hence these strata, in terms of their wide distribution in the section and laterally, may be prospective for shale oil exploration.